Character Education through Project-Based Learning: The Implementation of the Pancasila Student Profile and Rahmatan lil Alamin Project in an Islamic Elementary School - Purwanti, Kristi Liani; Adriyani, Zuanita; Afifa, Erlina Laily Nur; Nurhalisa, Siti (Journal of Integrated Elementary Education, 2025)
This study explores the implementation of the Pancasila student profile and rahmatan lil alamin project (P5 P2RA) within the Merdeka Curriculum at Madrasah Ibtidaiyah (MI) Taufiqiyah in Semarang, Indonesia—one of the pilot schools appointed by the Ministry of Religious Affairs to implement the Merdeka Curriculum. Employing a descriptive qualitative design, data were collected through interviews, observations, and documentation involving the principal, teachers, and program coordinator. The implementation of P5 P2RA at MI Taufiqiyah covers grades 1, 2, 4, and 5 and follows a structured process consisting of introduction, real action, reflection, and evaluation stages. The themes adopted in this project include local wisdom, sustainable lifestyle, and entrepreneurship, aligned with the character dimensions of belief in God, global diversity, creativity, independence, and mutual cooperation. Grounded in Lickona’s conception of character education and Kolb’s experiential learning model, the findings reveal significant development in students’ character. Students demonstrated increased responsibility, independence, gratitude to God, collaboration, environmental and social awareness, creativity, innovation, and self-confidence. The success of implementation was supported by strategic planning and integration of contextual values, leading to the emergence of a localized model of P5 P2RA suitable for Islamic elementary education. This study recommends strengthening implementation guidelines, expanding teacher training, and developing comprehensive assessment instruments to measure student character growth. The findings also support broader policy adoption to ensure that P5 P2RA effectively shapes students with Pancasila and rahmatan lil alamin values.